2004
DOI: 10.1152/japplphysiol.01160.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine on peripheral chemoreceptor activity in premature neonates: interaction with sleep stages

Abstract: Caffeine is widely used for the treatment of apnea in premature neonates. However, the localization of caffeine's target site (central nervous system and/or peripheral chemoreceptors) is not well defined, especially for sleeping neonates whose sleep stages interact with respiratory control. The aim of this study was to assess the activity of the peripheral chemoreceptors in relation to sleep stages in premature neonates treated (or not) with caffeine for idiopathic apnea. Peripheral chemoreceptor activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Neonates showed a pronounced decline inV E (Ϫ25%) in response to the hyperoxic test, as reported elsewhere (27,28). The ventilation decrease is detected at the RT, allowing measurement of the effectiveness of the peripheral chemoreceptors (22,23).…”
Section: Discussionsupporting
confidence: 75%
“…Neonates showed a pronounced decline inV E (Ϫ25%) in response to the hyperoxic test, as reported elsewhere (27,28). The ventilation decrease is detected at the RT, allowing measurement of the effectiveness of the peripheral chemoreceptors (22,23).…”
Section: Discussionsupporting
confidence: 75%
“…Although caffeine had only a small effect on respiratory muscle fatigue at sea level (Lanigan et al, 1993), its effect could be more pronounced at altitude, where ventilation is markedly increased from sea level and muscle fatigue is relatively more important. Caffeine has been used for decades in neonates for treatment of apnea (Comer et al, 2001;Chardon et al, 2004). At 4 mg=kg=day, it apparently works by increasing the effectiveness of chemoreceptor activity.…”
Section: Does Caffeine Depress Ventilation?mentioning
confidence: 99%
“…Prematurity, and specifically the 30 to 40 weeks post-menstrual age (PMA), is a critical developmental window for sleep-wake state organization, and the emergence of sustained arousal capacity. [9][10][11][12] Although two laboratories have failed to find effects of methylxanthines on sleep states in the premature, 13,14 behavioral indices of waking and temporal properties of movement were not studied. Thoman et al 12 found increased wake and decreased active sleep 8 weeks after cessation of theophylline treatment in preterm infants.…”
Section: Introductionmentioning
confidence: 99%